ASSOCIAÇÃO DE PREFERÊNCIAS VERSUS ILUMINAÇÃO AMBIENTAL POR MÚLTIPLA CORRESPONDÊNCIA - Tamura, Cintia; Krüger, Eduardo; Guimarães, André José Ribeiro (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Variations in ambient lighting settings can impact various subjective aspects of humans. In this context, the work raised, described and sought statistical associations between objective variables of ambient lighting conditions with subjective variables related to the light perception of individuals in a climate chamber. The use of multiple correspondence analysis (MCA) allowed the identification of significant correspondences, within the adopted criteria, only for the type of lighting and preferences regarding the lighting conditions in the time frame evaluated. Significant associations between season and light preference were not identified. Natural lighting has been shown to be preferred by the individuals of the sample, to the detriment of electric lighting. These findings are aligned with the literature, corroborating the innate human preference for natural light.